2003
DOI: 10.1074/jbc.m213134200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of 4-α-Glucanotransferase from Thermococcus litoralis and Its Complex with an Inhibitor

Abstract: Thermococcus litoralis 4-␣-glucanotransferase (TLGT) belongs to glucoside hydrolase family 57 and catalyzes the disproportionation of amylose and the formation of large cyclic ␣-1,4-glucan (cycloamylose) from linear amylose. We determined the crystal structure of TLGT with and without an inhibitor, acarbose. TLGT is composed of two domains: an N-terminal domain (domain I), which contains a (␤/␣) 7 barrel fold, and a C-terminal domain (domain II), which has a twisted ␤-sandwich fold. In the structure of TLGT co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 47 publications
4
107
0
6
Order By: Relevance
“…6) Our group has been trying to solve crystal structures of useful enzymes for use in bioindustry. Two of these were the first crystal structures within the GH42 and GH57 families, 7,8) and we then began to focus on CAZy enzymes belonging to structurally unknown families. We have since solved two more GH families, and provided the first crystal structures within GH54 and GH94.…”
mentioning
confidence: 99%
“…6) Our group has been trying to solve crystal structures of useful enzymes for use in bioindustry. Two of these were the first crystal structures within the GH42 and GH57 families, 7,8) and we then began to focus on CAZy enzymes belonging to structurally unknown families. We have since solved two more GH families, and provided the first crystal structures within GH54 and GH94.…”
mentioning
confidence: 99%
“…This length is close to that (6.7 A ) of T. litoralis 4 α glucanotransferase, the 3D structure of which is the only reported in the GH 57 family. 14) We found five residues (His10, His145, Trp270, Trp407 and Trp416) near the catalytic residues. These residues are all conserved in the TK1436 orthologs along with two catalytic residues.…”
Section: Structural Perspectivementioning
confidence: 99%
“…Regions A, B, C, E and F essentially correspond to the five conserved sequence motifs in the GH 57 family. 13) Two catalytic residues of the GH 57 family, initially identified in a series of biochemical and structural studies on Thermococcus litoralis 4 α glucanotransferase 14,15) and later shown to be conserved in other family members, 13,16) are located in Region C (Glu183, a nucleophile) and Region E (Asp354, an acid base catalyst). On the other hand, Region D is a region only conserved in the TK1436 subfamily.…”
Section: Primary Structure Of the Tk1436 Proteinmentioning
confidence: 99%
“…In the SCOP database (http://scop.mrclmb.cam.ac.uk/scop/) (21), the N-terminal domain has been classified into a galactose mutarotase-like superfamily with a super β-sandwich fold. Although the physiological function of the N-terminal domain is unclear, numerous glycosidases possessing the domain, such as GH57 4-α-glucanotransferase from Thermococcus litoralis (22), are classified into the same superfamily, suggesting that the super β-sandwich domain could bind to sugars.…”
Section: B Enzymes Belonging To Gh15: Glucoamylase and Glucodextranasementioning
confidence: 99%